Ritual Animals also Require Pedagogy, Communication, and Social Reasoning - Umbreș, Radu (Journal for the cognitive science of religion, 2020)
Harvey Whitehouse offers a complex and stimulating theory of rituals that bind people together and propagate via affiliative imitation. The Ritual Animal argues that fundamental problems of group cooperation can be solved by causally opaque and goal-demoted behaviors which produce arbitrary cultural conventions, honest signals of membership, and collective fused identities. This amply evidenced and compelling account explains a broad variety of prominent examples, yet other key causal mechanisms emerge from the ethnographic literature and analytical reflection on affiliation and groups. Taking a glance at some widespread and unusual rituals, this paper highlights the importance of cultural transmission via pedagogy with or without copying, costly signaling and coordination without coalitional groups, and meta-representations of impenetrable ritual efficacy. Future research can explain how bonding rituals become central features of social interaction without relying upon a quite debatable adaptive function of ritual behavior for cooperation - or anything else.